An overview of the intracellular localization of high-Z nanoradiosensitizers. (November 2022) - Varzandeh, Mohammad; Labbaf, Sheyda; Varshosaz, Jaleh; Laurent, Sophie
Abstract: Radiation therapy (RT) is a method commonly used for cancer treatment worldwide. Commonly, RT utilizes two routes for combating cancers: 1) high-energy radiation to generate toxic reactive oxygen species (ROS) (through the dissociation of water molecules) for damaging the deoxyribonucleic acid (DNA) inside the nucleus 2) direct degradation of the DNA. However, cancer cells have mechanisms to survive under intense RT, which can considerably decrease its therapeutic efficacy. Excessive radiation energy damages healthy tissues, and hence, low doses are applied for cancer treatment. Additionally, different radiosensitizers were used to sensitize cancer cells towards RT through individual mechanisms. Following this route, nanoparticle-based radiosensitizers (herein called nanoradiosensitizers) have recently gained attention owing to their ability to produce massive electrons which leads to the production of a huge amount of ROS. The success of the nanoradiosensitizer effect is closely correlated to its interaction with cells and its localization within the cells. In other words, tumor treatment is affected from the chain of events which is started from cell-nanoparticle interaction followed by the nanoparticles direction and homing inside the cell. Therefore, passive or active targeting of the nanoradiosensitizers in the subcellular level and the cell-nano interaction would determine the efficacy of the radiation therapy. The importance of the nanoradiosensitizer's targeting is increased while the organelles beyond nucleus are recently recognized as the mediators of the cancer cell death or resistance under RT. In this review, the principals of cell-nanomaterial interactions and which dominate nanoradiosensitizer efficiency in cancer therapy, are thoroughly discussed.